A morphological guide of neotropical freshwater sponge spicules for paleolimnological studies - Rasbold, Giliane G.; Calheira, Ludimila; Domingos-Luz, Leandro; Pessenda, Luiz C. R.; Pinheiro, Ulisses; McGlue, Michael M. (Frontiers in Ecology and Evolution, 2023)
Freshwater sponges (Porifera: Spongillida) are sessile invertebrates with skeletons composed of siliceous elements termed spicules. Sponge spicules (megascleres, microscleres, and gemmuloscleres) are characterized by widely varying sizes and shapes. These spicules are well-preserved in lacustrine, wetland, and riverine sediments and hold significant ecological and limnological information that can be applied as diagnostic tools in reconstructions of Quaternary environments. However, problems with taxonomy and the absence of systematic guidelines and standards of identification represent major challenges to utilizing freshwater sponges as a paleo-proxy. Here, we present a well-illustrated extraction protocol and morphological guide to the Neotropical freshwater sponge fauna. This guide is intended to introduce researchers and students to the study of freshwater sponges and their use as a diagnostic tool in paleoecology and paleolimnology.